Core Outcomes Set for Trials in People With Coronavirus Disease 2019. Issue 11 (November 2020) - Tong, Allison; Elliott, Julian H.; Azevedo, Luciano Cesar; Baumgart, Amanda; Bersten, Andrew; Cervantes, Lilia; Chew, Derek P.; Cho, Yeoungjee; Cooper, Tess; Crowe, Sally; Douglas, Ivor S.; Evangelidis, Nicole; et al.
Abstract : Objectives: The outcomes reported in trials in coronavirus disease 2019 are extremely heterogeneous and of uncertain patient relevance, limiting their applicability for clinical decision-making. The aim of this workshop was to establish a core outcomes set for trials in people with suspected or confirmed coronavirus disease 2019. Design: Four international online multistakeholder consensus workshops were convened to discuss proposed core outcomes for trials in people with suspected or confirmed coronavirus disease 2019, informed by a survey involving 9, 289 respondents from 111 countries. The transcripts were analyzed thematically. The workshop recommendations were used to finalize the core outcomes set. Setting: International. Subjects: Adults 18 years old and over with confirmed or suspected coronavirus disease 2019, their family members, members of the general public and health professionals (including clinicians, policy makers, regulators, funders, researchers). Interventions: None. Measurements: None. Main Results: Six themes were identified. "Responding to the critical and acute health crisis" reflected the immediate focus on saving lives and preventing life-threatening complications that underpinned the high prioritization of mortality, respiratory failure, and multiple organ failure. "Capturing different settings of care" highlighted the need to minimize the burden on hospitals and to acknowledge outcomes in community settings. "Encompassing the full trajectory and severity of disease" was addressing longer term impacts and the full spectrum of illness (e.g. shortness of breath and recovery). "Distinguishing overlap, correlation and collinearity" meant recognizing that symptoms such as shortness of breath had distinct value and minimizing overlap (e.g. lung function and pneumonia were on the continuum toward respiratory failure). "Recognizing adverse events" refers to the potential harms of new and evolving interventions. "Being cognizant of family and psychosocial wellbeing" reflected the pervasive impacts of coronavirus disease 2019. Conclusions: Mortality, respiratory failure, multiple organ failure, shortness of breath, and recovery are critically important outcomes to be consistently reported in coronavirus disease 2019 trials.